Suspect dyskeratotic neoformations in a 7-year-old child with keratitis-ichthyosis-deafness syndrome: diagnostic, surgical and wound care management - Alvise Montanari; Francesca Caroppo; Antonio Amabile; Anna Fortina Belloni; Franco Bassetto (PAGEPress Publications, 2024)
Keratitis-ichthyosis-deafness syndrome (KID) is a rare genetic disorder characterized by the triad of hyperkeratosis, ichthyosis, and congenital prelingual sensorineural deafness, with less than 100 cases described in the literature. In addition to many other extra-cutaneous manifestations, these patients are burdened by two principal increased risk factors involving the skin: the risk of developing infections and the risk of developing malignant skin tumors, especially Squamous Cell Carcinoma and Trichilemmal tumors. We present the case of a 7-year-old girl with a unique genetic variant described to date, who developed 4 dyskeratotic neoformation. Since the dermatoscopic examination was not sufficient to exclude malignancy, excisional and punch biopsies were used. Nonetheless, healing was challenging, with wound dehiscence and infection onset. Ad hoc wound care management resorting to negative pressure therapy and advanced medical honey-based dressings was necessary to achieve complete wound healing.